Hygroscopicity of internally mixed particles composed of (NH4)2SO4 and citric acid under pulsed RH change. (December 2017) - Shi, Xiao-Min; Wu, Feng-Min; Jing, Bo; Wang, Na; Xu, Lin-Lin; Pang, Shu-Feng; Zhang, Yun-Hong
Abstract: In this research, we applied a pulsed RH controlling system and a rapid scan vacuum FTIR spectrometer (PRHCS-RSVFTIR) to investigate hygroscopicity of internally mixed (NH4 )2 SO4 (AS)/citric acid (CA) particles. The water content and efflorescence ratio of AS in the particles and ambient relative humidity (RH) as a function of time were obtained with a subsecond time resolution. The hygroscopic behavior of AS aerosols in two different RH control processes (equilibrium and RH pulsed processes) showed that AS droplets crystallize with RH ranging from 42% to 26.5%. It was found that the half-life time ratio between the water content in the CA particles and the gas phase under RH pulsed change was greater than one under low RH conditions (<40% RH), indicating the significant water transfer limitation due to the high viscosity of CA aerosols at low RH, especially at RH<20%. In addition, water diffusion constants between 10 −12  m 2  s −1 and 10 −13  m 2  s −1 in micron size CA aerosols were obtained in a sub-second and second timescale. The addition of AS enhanced the water transfer limitation in the mixed aerosols. The efflorescence relative humidity (ERH) of the mixed particles with AS/CA by molar ratio 3:1 was found between 22.7% and 5.9%, which was much lower than AS particles. No efflorescence process was observed for the 1:1 mixed particles, indicating that CA greatly suppressed nucleation of AS. Our results have shown that the PRHCS-RSVFTIR is effective to simulate hygroscopicity and water transport of aerosols under fast variations in RH in atmosphere. Graphical abstract: Highlights: The RH pulse method can measure hygroscopicity of aerosols in time scale of seconds. Water diffusion coefficient in citric acid aerosols was obtained. The addition of citric acid suppressed crystallization of ammonium sulfate. Water transfer limitation was enhanced for the 1:3 mixture.